Choledochalcyst In Childhood (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objective.To Study Clinical Presentation, Management And Result Of  Treatment Of 11 Consecutive Case Of Choledochal Cyst Managed From 2012 To  2019. Method.11 Children Presented With Upper Abdominal Pain(72.72%), Jaundice(27.27%), Mass (18.18%). Ultrasonograpy  Diagnosed/Suugested In All 11 Children And Magnetic Resonance  Cholangiopancreatigram Suggsted In 11 Patient. Result.9 Patient From 11 Children Have Type 1a (Cystic Dilation).2 Patient Have  Type 1c(Fusiform Dilatation). Opertive Management Magement Included  Primary Complete Excision Of Choledochal Cyst With Roux-En-Y Hepaticodochojejeunostomy(N=9),And Cyst Excision With  Hepaticodochoduedenostomy(N=2).There Are 1 Post Operative Death Due To  Deep Icterus And Poor General Condition Prior To Surgery.Short Term Follow  Up Was Satisfactory In All 10 Patient. Conclusion.Choledochal Cyst Kept In Mind While Evalauting Children With  Reccurent Upper Abdominal Pain And Jaundice.Primary Excision Of Choledochal  Cyst With Roux-En Hepaticodochojejunostomy Providing Satisfactory Result  In Management Of Vast Majoratity Of Case Of Choledochal Cyst In Childhood.
Keywords: Choledochal Cyst; Abdominal Pain; Jaundice; Ultrasonograpy